2016
DOI: 10.1515/hsz-2015-0284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of microRNA-145 expression in renal cell carcinoma: a promising molecular marker for discriminating and staging the clear cell histological subtype

Abstract: The vast majority of malignancies detected in renal parenchyma are diagnosed as renal cell carcinoma (RCC), whose subtype discrimination and determination of prognosis may contribute to the selection of the adequate therapy. Recently, a new class of small non-coding RNAs, known as microRNAs, has proven to be among the most promising biomarkers for providing this information. Herein, we sought to add up to this knowledge by evaluating the expression levels of microRNA-145 (miR-145) in RCC. For that purpose, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In summary, lncRNAs serve important roles in the development and progression of cancers and may affect the survival prognosis of patients . The present study constructed a risk score model consisting of 5‐lncRNAs signature (AC009654.1, AC092490.2, LINC00524, LINC01234, and LINC01885), which may favor to evaluate the prognosis of ccRCC with superior predictive accuracy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, lncRNAs serve important roles in the development and progression of cancers and may affect the survival prognosis of patients . The present study constructed a risk score model consisting of 5‐lncRNAs signature (AC009654.1, AC092490.2, LINC00524, LINC01234, and LINC01885), which may favor to evaluate the prognosis of ccRCC with superior predictive accuracy.…”
Section: Discussionmentioning
confidence: 96%
“…In summary, lncRNAs serve important roles in the development and progression of cancers and may affect the survival prognosis of patients. 32,33 The present study constructed a risk score model consisting of 5-lncRNAs signature (AC009654.1, AC092490.2, LINC00524, LINC01234, and LINC01885), which may favor to evaluate the prognosis of ccRCC with superior predictive accuracy. The pathway enrichment indicated the PI3K-Akt-mTOR and HIF signaling pathways may be the most essential mechanisms mediated by the selected five lncRNAs, which needs to be further validated by well-performed experiments and cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment means were presented as the mean ± standard deviations of the mean using the three replicates [ 62 ]. Bioinformatics data were analyzed using R statistical software package in R Studio version 0.99.446 (RStudio, Inc. 2015) [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on mouse strains have shown that individual miRNAs or miRNA clusters are responsible for a range of diseases. It has been stated that low levels of mature miRNAs are linked to cancerous diseases [10] and miRNAs have been proven to be among the most promising biomarkers for providing information about cancer sub-type differentiation and prognosis [14]. For more details and an understanding of the miRNA and cancer correlation, please refer to [9].…”
Section: The Rna Sequence and Kidney Cancermentioning
confidence: 99%